1993
DOI: 10.1002/j.1460-2075.1993.tb06079.x
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian polypeptide chain release factor and tryptophanyl-tRNA synthetase are distinct proteins.

Abstract: A very high (approximately 90%) structural similarity exists between the bovine, human and murine tryptophanyl‐tRNA synthetases (WRS), and quite unexpectedly the rabbit polypeptide chain release factor (eRF). This similarity may point to a very close resemblance or identity between these proteins involved in distinct steps of protein synthesis, or inadvertently to an incorrect assignment of the clone reported to encode eRF, since the structure of clones encoding WRS were confirmed by peptide sequencing. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…If termination of translation in prokaryotes and eukaryotes is similar, one may anticipate the existence of a second eRF, since no GTP binding motifs were identified in eRFI (Frolova et al, 1994), while it has been demonstrated earlier that in mammals termination of translation is a GTP-dependent process (Beaudet and Caskey, 1971;Konecki et al, 1977). Furthermore, we have observed, after the last step of rabbit eRFI purification (Frolova et al, 1993b(Frolova et al, , 1994, that its activity decreases significantly and becomes GTP independent.…”
Section: Introductionmentioning
confidence: 90%
“…If termination of translation in prokaryotes and eukaryotes is similar, one may anticipate the existence of a second eRF, since no GTP binding motifs were identified in eRFI (Frolova et al, 1994), while it has been demonstrated earlier that in mammals termination of translation is a GTP-dependent process (Beaudet and Caskey, 1971;Konecki et al, 1977). Furthermore, we have observed, after the last step of rabbit eRFI purification (Frolova et al, 1993b(Frolova et al, , 1994, that its activity decreases significantly and becomes GTP independent.…”
Section: Introductionmentioning
confidence: 90%
“…The cloning of cDNA encoding the RF of a rabbit was reported in 1990 (Lee et al, 1990). A surprisingly high degree of similarity between the protein and tryptophanyl-tRNA synthetase identified served as evidence that the identified gene encodes the rabbit tryptophanyl synthetase but not the RF factor (Frolova et al, 1993). Even in early experiments, translation termination in mammals was demonstrated to be a GTP-dependent process (Beaudet and Caskey, 1971;Konecki et al, 1977), but to isolate a protein with GTPase activity was not possible.…”
Section: Geneticsmentioning
confidence: 99%
“…Although the presence of a rabbit reticulocyte release factor (eRF) was first shown 25 years ago, only recently have the protein and the gene been correctly identified. A gene previously thought to code for eRF (Lee et al, 1990) was finally shown to encode rabbit tryptophanyl-tRNA synthetase (Frolova et al, 1993). At present, it appears that a single polypeptide in eukaryotes (eRF1) fulfils the role of both of the prokaryotic factors RF1 and RF2, i.e.…”
Section: The Codon-specific Release Factorsmentioning
confidence: 99%